Local Mesh Refinement in 2 and 3 Dimensions - Bänsch, Eberhard (IMPACT of Computing in Science and Engineering, 1991)
An algorithm for local refinement of a given conforming triangulation in 2 or 3 dimensions is presented. Proofs for the finiteness of the algorithm and stability of the obtained triangulations are given. © 1991.
UnivIS-Import:2015-03-05:Pub.1991.nat.dma.lama3.localm